Combining Inorganic and Organic Carbon Stable Isotope Signatures in the Schwalbenberg Loess-Palaeosol-Sequence Near Remagen (Middle Rhine Valley, Germany) - Vinnepand, Mathias; Fischer, Peter; Fitzsimmons, Kathryn; Thornton, Barry; Fiedler, Sabine; Vött, Andreas (Frontiers in Earth Science, 2020)
Western Central European Loess-Palaeosol-Sequences (LPS) provide valuable terrestrial records of palaeoenvironmental conditions, which formed in response to variability in the North Atlantic climate systems. Over the last full glacial cycle (∼130 ka), climate oscillations within these systems are best documented in deep sea- and ice cores; the responses of terrestrial systems are not yet fully understood. A better understanding of metabolism governing input and output variables of organic- and inorganic C pools is, however, crucial for investigating landscape-atmospheric feedback processes and in particularly, for understanding the formation of calcareous LPS as environmental archives. Here we quantify the contributions of primary carbonates (PC) and secondary carbonates (SC) to the overall inorganic carbon pool down a LPS at the Schwalbenberg site, based on the natural abundance ratio of stable carbon isotopes (δ13C) and contents of the organic- and inorganic C pools. This facilitates detailed insights into the carbonate metabolism and hence, loessification and percolation processes. PC accumulate predominantly in cold phases during periods of reduced biological activity and become leached during wetter and warmer periods contemporary with higher rates of SC re-precipitation and total organic carbon (TOC) increases due to enhanced biomass production. We find that mineral dust input is most significant during stadials, as well as toward the end of warmer interstadials, characterised by gradual cooling back to stadial conditions. Pedogenesis in the Schwalbenberg LPS kept pace with surface accumulation of mineral dust. This indicates that palaeosols are of accretionary nature, which gives raise to the idea of incorporation of former topsoils in preserved subsoil horizons. Our study decodes fundamental aspects of the link between atmospheric dust circulation and terrestrial records in western Central Europe. In addition, interdependencies between factors governing the regional moisture budged and LPS can be reconstructed in a more holistic way than before.